Randomized trial of stopping or continuing ART among postpartum women with pre-ART CD4 ≥ 400 cells/mm3. - Judith S Currier; Paula Britto; Risa M Hoffman; Sean Brummel; Gaerolwe Masheto; Esau Joao; Breno Santos; Linda Aurpibul; Marcelo Losso; Marie F Pierre; Adriana Weinberg; Devasena Gnanashanmugam; et al. (PLoS ONE, 2017)
Health benefits of postpartum antiretroviral therapy (ART) for human immunodeficiency virus (HIV) positive women with high CD4+ T-counts have not been assessed in randomized trials.Asymptomatic, HIV-positive, non-breastfeeding women with pre-ART CD4+ T-cell counts ≥ 400 cells/mm3 started on ART during pregnancy were randomized up to 42 days after delivery to continue or discontinue ART. Lopinavir/ritonavir plus tenofovir/emtricitabine was the preferred ART regimen. The sample size was selected to provide 88% power to detect a 50% reduction from an annualized primary event rate of 2.07%. A post-hoc analysis evaluated HIV/AIDS-related and World Health Organization (WHO) Stage 2 and 3 events. All analyses were intent to treat.1652 women from 52 sites in Argentina, Botswana, Brazil, China, Haiti, Peru, Thailand and the US were enrolled (1/2010-11/2014). Median age was 28 years and major racial categories were Black African (28%), Asian (25%) White (15%). Median entry CD4 count was 696 cells/mm3 (IQR 575-869), median ART exposure prior to delivery was 19 weeks (IQR 13-24) and 94% had entry HIV-1 RNA < 1000 copies/ml. After a median follow-up of 2.3 years, the primary composite endpoint rate was significantly lower than expected, and not significantly different between arms (continue arm 0.21 /100 person years(py); discontinue 0.31/100 py, Hazard ratio (HR) 0.68, 95% CI: 0.19, 2.40). WHO Stage 2 and 3 events were significantly reduced with continued ART (2.08/100 py vs. 4.36/100 py in the discontinue arm; HR 0.48, 95%CI: 0.33, 0.70). Toxicity rates did not differ significantly between arms. Among women randomized to continue ART, 189/827 (23%) had virologic failure; of the 155 with resistance testing, 103 (66%) failed without resistance to their current regimen, suggesting non-adherence.Overall, serious clinical events were rare among young HIV-positive post-partum women with high CD4 cell counts. Continued ART was safe and was associated with a halving of the rate of WHO 2/3 conditions. Virologic failure rates were high, underscoring the urgent need to improve adherence in this population.ClinicalTrials.gov NCT00955968.